Development of the Android Application I-Findplace at University Tun Hussein Onn Malaysia (UTHM) - Shaffie, Nurshafinas; Hamid, Hashima (Research and Innovation in Technical and Vocational Education and Training, 2023)
This study was conducted to develop the I-Findplace Android Application at Universiti Tun Hussein Onn Malaysia (UTHM). This application was developed to guide users, especially in understanding the various locations around the campus and simultaneously performing location searches. The increasing number of students at UTHM has led to the development of the surrounding campus area, making it difficult for visitors or users to obtain information about each location within the UTHM campus. Therefore, the purpose of this study is to design, develop, and test the functionality of the I-Findplace Android Application. In this study, the developers utilized the constructivism learning theory and employed the waterfall model as a guide for the entire development process, which includes analysis, design, implementation, testing, and maintenance phases. After the Android application was developed, its functionality was evaluated using a questionnaire as an assessment tool, which was distributed to four (4) expert evaluators. Two evaluators assessed the content of the application, while the other two evaluated the user interface and multimedia elements. The research findings were analyzed, and positive feedback was obtained, indicating that the I-Findplace Android application at UTHM facilitates users in gaining a deeper understanding of specific locations and enables them to search for places around UTHM. Overall, the development of this application has achieved the predetermined objectives.